Okadaic acid (OA): Toxicity, detection and detoxification. (15th March 2019) - Fu, Ling-ling; Zhao, Xiao-yu; Ji, Lin-dan; Xu, Jin
Abstract: Okadaic acid (OA), a potent polyether marine toxin, accumulates in the digestive glands of marine mollusks and therefore can severely threaten the health of humans after ingestion of contaminated shellfish. In vivo and in vitro studies have revealed that exposure of various cells, including human embryonic amniotic cells, hepatocytes, neuroblastoma cells, to OA induces morphological and functional modifications as well as the death of cells. As the number of reports on OA poisoning has increased, this toxin has gradually attracted the public's attention, and researchers are trying to study it. This review summarizes the current literature on the toxicity effects of OA, in addition to its detection and detoxification.